Magiškasis realizmas sovietų okupacijos metais: Zigmunto Skujinio atvejis - Oga, Jānis (Colloquia, 2023)
A manifestation of magical realism in Latvian literature under the Soviet occupation was affected by literary and theoretical works available exclusively for the elite of the Soviet Union and publications in exile. In this article,1 the author focuses on the translations of literary works related to magical realism, available in Latvia during the Era of Stagnation, and their impact on the works of Latvian writers. The case study covers the work of Latvian writer Zigmunds Skujiņš, and particularly his novel Gulta ar zelta kāju (The Bed with a Golden Leg, 1984), one of the most essential Latvian novels written in the 1980s and also the most popular. Some critics have accented novel’s similarities with Gabriel García Márquez’s Cien años de soledad (One Hundred Years of Solitude, 1967) in the composition and poetics of the magic of the novel. In the novel written on the threshold of Latvian national independence, Skujiņš formally accepted Soviet modernity, though he was keen to follow and explore the paths that led to it, looking for the roots of modernity in the history of the Latvian nation and not the new order brought by its Soviet colonizers. A bestseller, the novel allowed Skujiņš to express essential ideas of non-violent resistance in colonial situation.
Keywords: latvių literatūra; stagnacija; perestroika; magiškasis realizmas; sovietinis turizmas; sovietų kolonializmas